Pelatihan Aplikasi Socrative bagi Guru dan Siswa Sebagai Upaya Meningkatkan Mutu Pembelajaran di SMKS YAPIM Siak Hulu Provinsi Riau - Afrizal, Johari; Yulianto, Yulianto; Ahmad, Arimulaini (Jurnal Pengabdian UNDIKMA, 2024)
This service activity aims to increase the knowledge and skills of teachers and students in using socrative as an effort to improve the quality of learning at Yapim Siak Hulu Vocational School, Riau Province. The method of implementing this service used training and mentoring with stages, namely preparation, implementation, and evaluation. The instrument of evaluation for this activity was a questionnaire which was analyzed descriptively. The results of this activity showed that teachers at Yapim Vocational School were able to use socrative, such as creating quizzes and running them online. Socrative also helped them assess students' abilities directly so they could provide feedback effectively. Meanwhile for students, Socrative had provided a new learning experience for them, learning that was fun and not boring. With this activity, it is hoped that it could help teachers improve their skills in the field of ICT while increasing their students' interest and motivation to learn.